Specification and guideline for technical aspects and scanning parameter settings of neonatal lung ultrasound examination. (4th March 2022) - Liu, Jing; Guo, Guo; Kurepa, Dalibor; Volpicelli, Giovanni; Sorantin, Erich; Lovrenski, Jovan; Alonso-Ojembarrena, Almudena; Hsieh, Kai-Sheng; Lodha, Abhay; Yeh, Tsu F.; Jagła, Mateusz; Shah, Heli; et al.
Abstract: Lung ultrasound (LUS) is now widely used in the diagnosis and monitor of neonatal lung diseases. Nevertheless, in the published literatures, the LUS images may display a significant variation in technical execution, while scanning parameters may influence diagnostic accuracy. The inter- and intra-observer reliabilities of ultrasound exam have been extensively studied in general and in LUS. As expected, the reliability declines in the hands of novices when they perform the point-of-care ultrasound (POC US). Consequently, having appropriate guidelines regarding to technical aspects of neonatal LUS exam is very important especially because diagnosis is mainly based on interpretation of artifacts produced by the pleural line and the lungs. The present work aimed to create an instrument operation specification and parameter setting guidelines for neonatal LUS. Technical aspects and scanning parameter settings that allow for standardization in obtaining LUS images include (1) select a high-end equipment with high-frequency linear array transducer (12–14 MHz). (2) Choose preset suitable for lung examination or small organs. (3) Keep the probe perpendicular to the ribs or parallel to the intercostal space. (4) Set the scanning depth at 4–5 cm. (5) Set 1–2 focal zones and adjust them close to the pleural line. (6) Use fundamental frequency with speckle reduction 2–3 or similar techniques. (7) Turn off spatial compounding imaging. (8) Adjust the time-gain compensation to get uniform image from the near-to far-field.